PENYULUHAN WAWASAN NUSANTARA DAN BELA NEGARA UNTUK GENERASI MARITIM YANG TANGGUH DAN BERKARAKTER - Toto Suryadi; Widiya Amalia; Hendri Kustian (SWADIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
The "National Insight and National Defense for a Resilient and Characterful Maritime Generation" outreach activity was carried out as a form of community service by the Jakarta Maritime Development Academy. This activity aims to instill and strengthen national values, national defense awareness, and students' understanding of the concept of the National Insight in the context of Indonesian maritime affairs. The phenomenon of the young generation's limited understanding of national values and national defense serves as the background to this activity, in which many students still view the spirit of national defense solely as a military matter, rather than as a citizen's responsibility in everyday life. Therefore, this seminar seeks to link national insight with sailors' character and identity as guardians of the nation's maritime sovereignty. The activity methods include interactive delivery of material, group discussions, and reflection on national values, involving students, teachers, and resource persons from academia and maritime practitioners. Based on the evaluation results, this activity succeeded in increasing students' understanding of the concepts of National Insight and National Defense by 32% and in fostering an attitude of nationalism and national responsibility among participants. The results of the activity indicate that this kind of outreach is effective in building national defense awareness among the young maritime generation. In addition, this activity involves unlocking the potential for sustainability through fostering extracurricular national defense programs, integrating national values into the maritime curriculum, and developing partnerships between maritime educational institutions and defense agencies. Thus, this seminar significantly contributes to the development of a maritime generation that is resilient, has character, and possesses a strong spirit of national defense, in line with the national development vision for maritime affairs and national resilience.Kegiatan penyuluhan Wawasan Nusantara dan Bela Negara untuk Generasi Maritim yang Tangguh dan Berkarakter” dilaksanakan sebagai bentuk pengabdian kepada masyarakat oleh Akademi Maritim Pembangunan Jakarta. Kegiatan ini bertujuan untuk menanamkan dan memperkuat nilai-nilai kebangsaan, kesadaran bela negara, serta pemahaman peserta didik terhadap konsep Wawasan Nusantara dalam konteks kemaritiman Indonesia. Fenomena rendahnya pemahaman generasi muda terhadap nilai kebangsaan dan bela negara menjadi latar belakang kegiatan ini, di mana banyak pelajar masih memandang semangat bela negara hanya sebatas aspek militer, bukan sebagai tanggung jawab warga negara dalam kehidupan sehari-hari. Oleh karena itu, seminar ini berupaya mengaitkan wawasan kebangsaan dengan karakter dan jati diri pelaut sebagai penjaga kedaulatan maritim bangsa. Metode kegiatan meliputi penyampaian materi interaktif, diskusi kelompok, dan refleksi nilai kebangsaan dengan melibatkan siswa, guru, dan narasumber dari kalangan akademisi dan praktisi maritim. Berdasarkan hasil evaluasi, kegiatan ini berhasil meningkatkan pemahaman siswa terhadap konsep Wawasan Nusantara dan Bela Negara sebesar 32%, serta menumbuhkan sikap nasionalisme dan tanggung jawab kebangsaan di kalangan peserta. Hasil kegiatan menunjukkan bahwa penyuluhan semacam ini efektif dalam membangun kesadaran bela negara bagi generasi muda maritim. Selain itu, kegiatan ini membuka potensi keberlanjutan berupa pembinaan ekstrakurikuler bela negara, integrasi nilai kebangsaan dalam kurikulum pelayaran, serta pengembangan kemitraan antara institusi pendidikan maritim dan instansi pertahanan. Dengan demikian, seminar ini berkontribusi nyata dalam upaya membentuk generasi maritim yang tangguh, berkarakter, dan memiliki semangat bela negara yang kuat, sejalan dengan visi pembangunan nasional di bidang kemaritiman dan ketahanan bangsa